Possessed persons - useful ritual functonaries? - Dragana Antonijević (University of Belgrade, 2016)
Review of the book by Danijel Sinani, Opsednutost i egzorcizam u Srbiji. Antropološki pristup (The Obsession and the Exorcism in Serbia. Anthropological Approach), Srpski genealoški centar i Odeljenje za etnologiju i antropologiju Filozofskog fakulteta u Beogradu, knj. 31, Beograd, 2007, str. 190.